Affect of PGPR Concentration (Plant Growth Promoting Rhizobacteria) on Growth and Yield of Some Sorghum Varieties in Dry Land - Ilwati, Uun; Ujianto, Lestari; Suwardji, Suwardji (Indonesian Journal of Agriculture and Environmental Analytics, 2025)
This study aims to determine the effect of PGPR concentration and sorghum variety on the growth and yield of sorghum plants. The experimental design used in this study was a randomised block design with a factorial experiment. This experimental design consisted of two factors, namely PGPR concentration (K0 without PGPR, K1 with 20 ml/l PGPR per plant, K2 with 40 ml/l PGPR per plant, and K3 with 60 ml/l PGPR per plant) and sorghum variety (V1 is the Soper 9 variety, V2 is the SR2401 variety, and V3 is the SR2404 variety). Based on the analysis of the research results, it was found that PGPR concentration and sorghum variety significantly influenced several sorghum growth parameters, including the number of leaves, leaf area, and stem diameter, but did not significantly differ in plant height. For sorghum yield parameters, concentration and variety significantly influenced 1000-seed weight, root length, panicle length, seeds per panicle, wet weight, and Brix content. The interaction between PGPR concentration and sorghum variety significantly influenced seeds per panicle. A PGPR concentration of 60 ml/l yielded higher results compared to other concentrations, and the SR2404 variety had a significant effect on all observed parameters. It is hoped that this study can serve as a reference and guideline for farmers and the general public in determining the variety and PGPR concentration to be used in sorghum cultivation on dry land.